If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3/5)+z=1
We move all terms to the left:
(3/5)+z-(1)=0
determiningTheFunctionDomain z-1+(3/5)=0
We add all the numbers together, and all the variables
z-1+(+3/5)=0
We get rid of parentheses
z-1+3/5=0
We multiply all the terms by the denominator
z*5+3-1*5=0
We add all the numbers together, and all the variables
z*5-2=0
Wy multiply elements
5z-2=0
We move all terms containing z to the left, all other terms to the right
5z=2
z=2/5
z=2/5
| y2-8y=0 | | 2x^2-50x+128=0 | | –7+u/6=0 | | 2(f+-7)=6 | | –7+u6=0 | | -4(f+1)=12 | | (5x-4)(2x-7)=0 | | b=40-9b | | 12+y3=15 | | 25=k÷5 | | 12+5t=4t | | -6(1-m)=0-2m | | 1/4k-6=3 | | -4(4x+5)=124 | | 45=(2w+1)w | | 47=10r+17 | | -5(-1+5x)=-20 | | 6m-3+7=9 | | 5(4-6x)=170 | | -10x+4=-8x | | 3-2/b=1/3bb-7 | | 7h=-1(2h+18) | | x/465.3=16.5 | | 20=n/611 | | x/16.5=465.3 | | 4/n−2=5 | | 7k/3=27 | | r+6r+6-5r=14-2r | | 5/m−3=8 | | 1/3x+1/4=-3(5/6x-1) | | –z/3–9=–7 | | 0/4t=0.72 |